Differences in perceived causes of childhood obesity between migrant and local communities in China: a qualitative study. (October 2016) - Li, Bai; Lin, Rong; Liu, Wei; Chen, Jingyi; Liu, Weijia; Cheng, Kar Keung; Pallan, Miranda; Adab, Peymane; Jones, Laura
Abstract: Background: In China, obesity has traditionally affected the more affluent urban children, but the problem is spreading to a wider social group, including children who have migrated from rural to urban areas. Customised interventions are needed to prevent further growth in the prevalence of obesity among these migrant children. Exploring the perceptions of key stakeholders regarding the causes of childhood obesity can provide valuable insights, but no qualitative studies have addressed this issue. We investigated the differences in the perceived causes of childhood obesity between local and migrant communities living in a major city in China. Methods: We conducted 20 focus groups (six in migrant communities) involving 137 participants (including parents, grandparents, and school teachers) and 11 semi-structured interviews with school principals (two from schools for migrants) in Guangzhou. Audio data were transcribed verbatim and analysed with a thematic approach. Ethics approval was obtained from the Life and Health Sciences Ethical Review Committee at the University of Birmingham (reference ERN_13-1519). Local ethics approval was also granted by the Ethical Committee of Guangzhou Center for Disease Control and Prevention. Findings: Three potential protective factors for obesity among migrant children were interpreted (theme one). Grandparents remaining in the hometown of migrant families were not believed to influence child care that often promotes obesity among local children. Migrant children might be exposed to fewer opportunities for unhealthy snacking and had more opportunity for active play, as they were reportedly under less pressure for academic attainment compared with local children. Nevertheless, two perceived causes were more pronounced for migrant children than for local children (theme two): a lack of parental care and monitoring for after-school health behaviours; and unsafe neighbourhoods with insufficient space for physical activity. Two further barriers that restricted children's physical activity were only found in the migrant community (theme three): limited home space for physical activity, and cultural differences that made interactive play with local children challenging. Interpretation: Although migrant children might have benefited from some protective factors in relation to the development of childhood obesity, several perceived causes were either more pronounced or unique in relation to this group. Future research should deepen knowledge of the modifiable determinants of obesity in migrant children and develop appropriate intervention strategies to prevent further rise of the epidemic in this population while continuing current efforts to control obesity in local children. Funding: The study was funded by theGuangzhou Medical Foundation (20131A031001 ).